(untitled) (Innovative Technologica: Methodical Research Journal, 2023)
Russian Russian the article discusses techniques and methods of increasing motivation among foreign-speaking schoolchildren when studying the vocabulary of the modern Russian language, and also provides lexical tasks that help the teacher to increase motivation to learn Russian in a foreign-speaking audience.